Effect of Surface Coatings on Thermal performance of steel Substrates. (2017) - Sreenivasa Rao, K.V.; Girisha, K.G.; Pooja Shree, R; Kumar, Manish
Abstract: Surface coatings not only serve as the barrier between the substrate and the adverse operating conditions like wear and corrosion, they also have a decided effect on the thermal performance of the underlying base materials. The present work evaluates the effect of ZrO2, Cr2 O3 and TiO2 coating on the thermal properties of the substrate material. Plasma spray technique was adopted for depositing the desired powder particles on the steel plate substrate. The steel plate was heated in a controlled experimental set-up from the coated side while the other side was insulated. K-type thermocouples interfaced with temperature data acquisition system were used to record the time-temperature history of the steel plate. The recorded temperature data was used to analyze the effect of surface coatings on conduction heat transfer across the substrate materials. The results clearly indicate a drastic variation in conduction heat transfer in the underlying steel substrate due to coating. Among the three coating powders, ZrO2 exhibits higher resistance for thermal conduction across the material.